Designing media - Moggridge, Bill. (Cambridge, Mass. : MIT Press, 2010)
Mainstream media have not yet disappeared in a digital takeover of the media landscape. But the long-dominant media-- television, radio, newspapers, magazines, and books-- have had to respond to emergent digital media. In Designing Media, Bill Moggridge examines connections and conflicts between old and new media, describing how the mainstream media have changed and how new patterns of media consumption are emerging. The book features interviews with thirty-seven significant figures in both traditional and new forms of mass communication. Accompanying DVD includes excerpts from all the interviews.
Here to stay (interviews with Paul Saffo, James Truman, Chris Anderson, Neil Stevenson, DJ Spooky) -- Yes we can (interviews with Jimmy Wales, Craig Newmark, Tim Westergren, Blixa Bargeld with Erin Zhu, Airside, Roger McNamee) -- New connections (interviews with Jorge Just, Chad Hurley, Alexandra Juhasz, Bob Mason with Jeremy Merle, Ev Williams, Mark Zuckerberg -- Both worlds (interviews with Joel Hyatt, Bruce Nussbaum, Jessie Scanlon, Jane Friedman, Martin Eberhard, Rich Archuleta) -- Content is king (interviews with Arthur Sulzberger Jr., Alice Rawsthorn, Ira Glass, Colin Callender) -- Let the truth be told (interviews with David Fanning, Mark Gerzon, Shinichi Takemura, Hans Rosling with Ola Rosling & Anna Rosling R$1)2q(Bnnlund).s
Book is accompanied by one CD/diskette, entitled' Designing media' bearing the same call number and available at Bahabian Koleksi Media.
Includes bibliographical references and index.
Keywords: Digital media design -- Interviews; Multimedia systems; Mass media